1993
DOI: 10.1111/j.1365-2958.1993.tb01179.x
|View full text |Cite
|
Sign up to set email alerts
|

Organization of Lrp‐binding sites upstream of ilvlH in Salmonella typhimurium

Abstract: Lrp, a major regulatory protein in Escherichia coli, controls the expression of numerous operons, including ilvIH. Lrp binds to six sites upstream of ilvIH, and Lrp binding is required for ilvIH expression. We show here that an Lrp-like protein is also present in Salmonella typhimurium. This protein can bind both E. coli and S. typhimurium ilvIH DNA, as can E. coli Lrp. Methidiumpropyl-EDTA footprinting studies were performed with purified E. coli Lrp and S. typhimurium ilvIH DNA. Six binding sites were define… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
26
0

Year Published

1994
1994
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 17 publications
1
26
0
Order By: Relevance
“…Fig. 3B) (28,30), and a similar consensus was derived by Rex et al from a comparison of sequences of Lrp-related genes (21). Within the sequence shown in Fig.…”
Section: And C [Compare Fragments F-hb F-rb and F-hr])mentioning
confidence: 90%
See 1 more Smart Citation
“…Fig. 3B) (28,30), and a similar consensus was derived by Rex et al from a comparison of sequences of Lrp-related genes (21). Within the sequence shown in Fig.…”
Section: And C [Compare Fragments F-hb F-rb and F-hr])mentioning
confidence: 90%
“…A mutational analysis showed that the N-terminal third of Lrp is responsible for DNA binding, the middle third mediates transcriptional activation, and the C-terminal third determines the response of Lrp to leucine (19). In vitro, Lrp binds in a sequence-specific fashion to multiple sites upstream of the ilvIH promoters from E. coli and Salmonella typhimurium (28,30) and bends DNA upon binding (29). Binding of Lrp to these sites is both necessary and sufficient for transcriptional activation of the ilvIH operon (31).…”
mentioning
confidence: 99%
“…If in fact each GACTN NNAGTC is bound by a C protein dimer, the center-to-center distance of 15 bp for the two sites means that the two dimers would occupy opposite faces of the double helix. This pattern of multiple binding sites, all with the same polarity, on two faces of the double helix is also seen with another transcriptional activator-the leucine-responsive regulatory protein (Lrp) of E. coli (56,62,64). Lrp, like the C proteins, is a small dimeric protein with a predicted helix-turn-helix motif that recognizes a symmetrical sequence with a central A/T triplet (21,51,56).…”
Section: Discussionmentioning
confidence: 99%
“…Although the DNA sequence of the corresponding region in E. coli is different, the average A + T content is the same (Haughn et al 1986) and the promoter relay is conserved in both species . Another DNA binding protein, the leucine-responsive regulatory protein, Lrp, contributes by stimulating transcription of P ilvIH (Wang et al 1993) A gene may not have to leave its original host cell to experience new patterns of DNA topological influence. Simply repositioning the gene on the single, circular chromosome of the bacterium may achieve this effect (Brambilla and Sclavi 2015;Fitzgerald et al 2015;Gerganova et al 2015).…”
Section: Dna Supercoiling Bacterial Evolution and Pathogenesismentioning
confidence: 99%